Oltre il melodramma: Una teoria del dramma musicale (Materiali di Estetica. Terza serie, 2020)
In this paper I consider one of the most studied themes by Gabriele Scaramuzza, who has been a full professor of Aesthetics at the University of Milan. The starting point of his reflections is constituted by the French melodrama of the late Eighteenth century, to arrive at the Nineteenth-century musical drama, which preserves some codes of the first, while restructuring their meaning. In particular, Verdi's production contains some very high moments, for which some critics have openly compared him to Shakespeare, even if his works contain popular elements, easily perceptible by a non-professional audience. Basically, his work expresses "the sensible appearance of an idea", which does not only concern the professional elites, but involves all the Risorgimental Italy. It demonstrates in an Hegelian attitude "the ability of the art to shape an entire society and find a correspondence in it”, far beyond an intellectualistic understanding, which is appreciated by some critics, but has already been reproved by such authors as A. Banfi. This is the field to which Scaramuzza has dedicated several texts, shedding light on a complex and articulated topic.
Keywords: Musical drama; G. Scaramuzza; W. Shakespeare; G. Steiner; G. Verdi